2015
DOI: 10.4236/ojped.2015.53039
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis in Children with Sickle Cell Disease in Ouagadougou Pediatric Hospital

Abstract: Introduction: Sickle cell disease (SCD) causes chronic hemolysis which is a risk factor for cholelithiasis. Its development may lead to severe and life-threatening complications. Objective: Determine the prevalence of cholelithiasis, the conditions of diagnosis and related factors. Materials and Method: We retrospectively reviewed records of 110 patients with sickle cell disease followed up in Charles de Gaulle University Pediatric Hospital from January 2003 to December 2013, including 103 patients who had abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
1
2
1
Order By: Relevance
“…In contrast to our findings, Koueta et al [42] found the prevalence of Cholelithiasis to be 24.3% among children with sickle cell anaemia in Burkina Faso (West Africa), despite having a study population and perhaps environmental factors similar to this study. The higher prevalence they reported compared to this and others within sub-Saharan Africa may be attributable to differences in study design; the Burkina Faso study was a 10 year retrospective review of abdominal ultrasound reports from their clinic over ten years.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Koueta et al [42] found the prevalence of Cholelithiasis to be 24.3% among children with sickle cell anaemia in Burkina Faso (West Africa), despite having a study population and perhaps environmental factors similar to this study. The higher prevalence they reported compared to this and others within sub-Saharan Africa may be attributable to differences in study design; the Burkina Faso study was a 10 year retrospective review of abdominal ultrasound reports from their clinic over ten years.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, in our series, patients who have been transfused more than three times since birth were 3 times more likely to develop cholelithiasis. The same observation was made by Koueta in Burkina Faso [ 14 ]. In the USA, a study on the effects of chronic transfusions on abdominal sonographic abnormalities in children with sickle cell anemia reported that gallbladder disease was correlated with older age ( p =0.002), longer duration of transfusions ( p =0.034), and higher total bilirubin ( p ≤ 0.001) [ 15 ].…”
Section: Discussionsupporting
confidence: 80%
“…No significant association was found between VOC frequency and the occurrence of LB. Koueta reported a significant risk (OR = 7.6) when children had at least three VOCs per year [ 14 ]. Alhawsawi in Saudi Arabia and Martins in Brazil reported similar results to ours with a higher prevalence of LB in children of phenotype SS compared to S β -thalassemias and SC without the difference being significant [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the literature search retrieved 1135 published articles. After exclusion of studies because of irrelevance and insufficient data to estimate the outcomes of interest, a total of 34 eligible studies published from 1977 to 2020, which met the eligibility for data extraction and analyses, were used for qualitative and quantitative synthesis; 15 studies from Africa, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 seven studies from the South America and North America, 42 , 43 , 44 , 45 , 46 , 47 , 48 seven studies from Asia, 8 , 49 , 50 , 51 , 52 , 53 , 54 and four studies from Europe. 55 , 56 , 57 , 58 Overall, this analysis included a total of 6771 SCD patients.…”
Section: Resultsmentioning
confidence: 99%